LUKA SEJARAH YANG TERSEMBUNYI: KISAH JUGUN IANFU DI MASA PENDUDUKAN JEPANG - Rosmaida, Rosmaida Sinaga; Fifi, Fifi Fathia; Sarah, Sarah Clarissa Hutagalung; Tiarma, Tiarma Elisabet Nainggolan; Amelia, Amelia Anggi Owein Bintang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article, titled “Hidden Historical Wounds: The Story of Jugun Ianfu during the Japanese Occupation,” analyzes the practice of sexual slavery against Indonesian women during the Japanese occupation (1942–1945). The Jugun Ianfu system was well organized through the establishment of comfort stations (ianjo) for the benefit of the Japanese military. The recruitment process was carried out through fraudulent means, such as deception, coercion, intimidation, and even kidnapping, which resulted in many Indonesian women—including those who were very young—suffering both physically and mentally. The consequences were not only related to sexual violence and prolonged trauma, but also the social stigma they faced after returning to their communities. Using historical, sociological, and narrative analysis approaches, this study attempts to uncover a tragedy that is often ignored as a “national disgrace.” The results of the study show that Jugun Ianfu was not only a manifestation of Japanese hegemony over women, but also left deep historical wounds and became an important lesson to prevent similar atrocities from recurring in the future.